Determining Relative Bioavailability of Trace Minerals When Incorporated into Mollasses-Based Block Supplements - Trigo, Elisa; Drouillard, James S. (My University, 2016)
Introduction Experimenting trace elements, including copper, manganese, and zinc incorporated into molasses-based block supplements. Assessing the impact of the block process on the ability to increase bioavailability when incorporated into molasses-based block supplements to increase the productivity of a beef cattle production. Objectives Measure the relative bioavailability of trace elements in 0, 1, and 5 times NRC recommendations through measuring in vitro results of volatile fatty acid (VFA) gas production, and in vitro dry matter disappearance by cultures of mixed ruminal microbes. Materials and Methods The study was conducted on October 22nd, 2016, as a randomized complete block design using a 2 x 3 factorial arrangement of treatments with 4 replicates. Factor 1 was comprised of trace mineral concentration (0, 1, or 5 times of NRC recommendations based on total substrate weight). Factor 2 consisted of the form in which the mineral is added (incorporated into molasses block) or added separate from the molasses block. In preparation for the in vitro experiment all substrates were weighed and added to 24 fermentation bottles. Substrate contents of 20 grams of prairie hay and 5 grams of alfalfa hay. Additionally, 1 gram of the appropriate block supplement was added to each bottle (0x, 1x, or 5x). Additionally, 1 mL of H2O or 1 mL of the appropriate mineral solution (diluted in H2O) was added to each bottle suing a 1-mL pipette. Trace mineral solutions (in H2O) were prepared by incorporating appropriate amounts of zinc sulfate, copper sulfate, and magnesium sulfate into distilled/deionized water. McDougall’s buffer was prepared the day prior (20 L) on the 21st of October. Ruminal fluid was taken from four ruminally-fistulated donor animals as the source of bacteria rich microbial inoculum used in the in vitro cultures. McDougall’s buffer and the ruminal fluid were added to each bottle and allowed to ferment for a period of 24 hours. Following incubation, pressure was released from bottles using the Global Pressure Release on the ATKOM RF Gas Production System, and pH was recorded for each bottle. For volatile fatty acid analysis, the supernatant fraction was transferred to gas chromatography vials and measured using a gas chromatograph. Conclusion The overall objective of this study was comparing the bioavailability of minerals when incorporated inside a molasses block compared to water. The effect of the molasses block was not statistically significant enough to affect the productivity of a steer; meaning that the hypothesis was rejected.
Keywords: Fall 2016